2018
DOI: 10.1186/s12913-018-3463-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting respectful maternity care in rural Tanzania: nurses’ experiences of the “Health Workers for Change” program

Abstract: BackgroundDisrespectful and abusive care of women during their pregnancies has been shown to be a barrier for women accessing health care services for antenatal care and delivery. As part of an implementation research study to improve women’s access to health care services in Rorya District, Mara, Tanzania, we conducted a pilot study training reproductive health care nurses to be more sensitive to women’s needs based on the “Health Workers for Change” curriculum.MethodsSix series of workshops were held with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 11 publications
3
31
0
Order By: Relevance
“…The WHO has developed a quality of care framework for pregnant women and newborns in facilities, which highlights the overarching need for both competent human resources and essential physical resources and additionally requires evidence-based practices for routine and emergency care; actionable information systems; functional referral systems; effective communication; respect and dignity; and emotional support [ 57 ]. In recent years, increased emphasis has been placed on promotion of respectful maternity care and elimination of abuse during childbirth [ 58 – 60 ]. One study found that women who experience discrimination or abuse during childbirth are less likely to seek facility-based delivery care in the future [ 61 ]; such experiences may also deter postnatal care-seeking [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO has developed a quality of care framework for pregnant women and newborns in facilities, which highlights the overarching need for both competent human resources and essential physical resources and additionally requires evidence-based practices for routine and emergency care; actionable information systems; functional referral systems; effective communication; respect and dignity; and emotional support [ 57 ]. In recent years, increased emphasis has been placed on promotion of respectful maternity care and elimination of abuse during childbirth [ 58 – 60 ]. One study found that women who experience discrimination or abuse during childbirth are less likely to seek facility-based delivery care in the future [ 61 ]; such experiences may also deter postnatal care-seeking [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The training program had a positive impact on the quality of counseling family planning services, providers' interpersonal skills and overall knowledge (38). This is supported by a pilot study training reproductive health care nurses on promoting respectful maternity care which concluded that the training has positive impact on promoting respectful care (39).…”
Section: Discussionmentioning
confidence: 88%
“…And we have to do it with our heart, that is most important." (Midwife, FGD 5, age group [41][42][43][44][45][46][47][48][49][50] Most women are also satis ed and happy after the delivery, and especially at the maternity ward the contact with women was told to be positive.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, midwives' educational curriculum should include proper training about (pain) mechanisms during labour for avoiding such negative reasoning that might constitute to D&A. Some promising results have been found from the implementation of a workshop called "Health Workers for Change" in Tanzania covering re ection and discussion about different topics such as own values, women's status in society and overcoming obstacles at work [50]. The Population Council's Heshima Project in Kenya successfully used a similar approach [51].…”
Section: Discussionmentioning
confidence: 99%